Analisis pengaruh media sosial terhadap keputusan pembelian study kasus : skincare wardah - Suryani Suryani; Khairina Tambunan; Purnama Ramadhani Silalahi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Currently, the development of industry in Indonesia, especially cosmetics is growing rapidly. The purpose of this study was to determine the effect of social media on purchasing decisions. Case study: skincare wardah. The method used in this research is quantitative method. The type of data used in this research is primary data. The population of this study were all users of Wardah products in North Sumatra. Data collection techniques used in this study by distributing questionnaires to respondents either directly or indirectly. The result of the research is that social media variables have a significant effect on purchasing decisions. The purchasing decision indicator that has the highest average value is the willingness to sacrifice.